2006
DOI: 10.1097/01.wnr.0000198434.06518.b8
|View full text |Cite
|
Sign up to set email alerts
|

Widespread functional disconnectivity in schizophrenia with resting-state functional magnetic resonance imaging

Abstract: Using resting-state functional magnetic resonance imaging, we examined the functional connectivity throughout the entire brain in schizophrenia. The abnormalities in functional connectivity were identified by comparing the correlation coefficients of each pair of 116 brain regions between 15 patients and 15 controls. Then, the global distribution of the abnormal functional connectivities was examined. Experimental results indicated, in general, a decreased functional connectivity in schizophrenia during rest, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
249
2
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 369 publications
(292 citation statements)
references
References 23 publications
38
249
2
3
Order By: Relevance
“…A recent functional connectivity study examined fMRI timeseries correlations between all combinations of 116 brain regions and found that, except for increased cerebellar connectivity, schizophrenia subjects in a resting state exhibited global reductions in functional connectivity (Liang et al, 2006). Other studies using timeseries correlations have focused on different specific connections, and identified abnormalities in the connectivity of the cerebellum (Stephan et al, 2001) and anterior cingulate (Honey et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A recent functional connectivity study examined fMRI timeseries correlations between all combinations of 116 brain regions and found that, except for increased cerebellar connectivity, schizophrenia subjects in a resting state exhibited global reductions in functional connectivity (Liang et al, 2006). Other studies using timeseries correlations have focused on different specific connections, and identified abnormalities in the connectivity of the cerebellum (Stephan et al, 2001) and anterior cingulate (Honey et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The activity is similar to that observed during stimulus presentation (1,(6)(7)(8), incorporates previously acquired information (9), and carries information about the underlying neuronal network [for review see (10)]. Indeed, correlations during resting state activity are altered in disease states such as schizophrenia or chronic pain (11,12), which raises the question whether there is a general framework that describes the statistics in the spatiotemporal organization of this dynamics.…”
mentioning
confidence: 97%
“…Although brain functions proposed for the DMN are impaired in patients with schizophrenia (Buckner et al, 2008), neuroimaging studies have reported inconsistent findings in the DMN of these individuals. Increased (Garrity et al, 2007;Harrison et al, 2007;Whitfield-Gabrieli et al, 2009;Zhou et al, 2007) or decreased (Liang et al, 2006;Pomarol-Clotet et al, 2008) activity and connectivity have been reported in the DMN network at the level of individual regions as well as of the global network. Different issues may have contributed to lack of consistent findings, including the method used for estimation of connectivity (Murphy et al, 2009).…”
Section: Introductionmentioning
confidence: 99%